Protocol to Design, Clone, and Validate sgRNAs for In Vivo Reverse Genetic Studies - Hunker, Avery C. (STAR Protoc, 2020)
AAV-CRISPR/Cas9 permits gene mutagenesis in the adult CNS. Current methods determining in vivo on-target mutagenesis have been limited by the ability to isolate virally transduced cells. This protocol optimizes a workflow for the design, cloning, and validation of sgRNAs delivered by AAVs in vivo that can be applied to any target gene in the CNS of rat or mouse model systems and can be adapted to Cre or Flp driver lines using AAV-FLEX-SaCas9-sgRNA or AAV-FLEXfrt-SaCas9-sgRNA, respectively. For complete details on the use and execution of this protocol, please refer to Hunker et al. (2020).